1996
DOI: 10.1109/55.511586
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency noise characterization of n- and p-MOSFET's with ultrathin oxynitride gate films

Abstract: Abstruct-MOSFET's with ultrathin (5 to 8.5 nm) silicon oxynitride gate film prepared by low-pressure rapid thermal chemical vapor deposition (RTCVD) using SiH4, NzO and NH3 gases, are studied by low-frequency noise measurements (1 Hz up to 5 kHz). The analysis takes into account the correlated mobility fluctuations induced by those of the interfacial oxide charge. The nitrogen concentration, determined from SIMS analysis, varies from 0 to 11% atomic percentage. A comparison of the electrical properties between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 12 publications
3
34
0
Order By: Relevance
“…Moreover, it is worth noting that noise levels are higher in p-MOSFETs, even in the reference devices. This result is in agreement with the study of Morfouli et al [22]. They reported that in the case of SiON dielectric, p-MOSFETs show a larger trap density with respect to the n-MOSFETs.…”
Section: Impact Of Gate Electrodesupporting
confidence: 93%
See 1 more Smart Citation
“…Moreover, it is worth noting that noise levels are higher in p-MOSFETs, even in the reference devices. This result is in agreement with the study of Morfouli et al [22]. They reported that in the case of SiON dielectric, p-MOSFETs show a larger trap density with respect to the n-MOSFETs.…”
Section: Impact Of Gate Electrodesupporting
confidence: 93%
“…Under this supposition, the trap density N t can be extracted by using (1), and the results are shown in Fig. 4 [22], [23]. Therefore, an increase of defectivity in the gate dielectric is observed in both high-k materials with respect to conventional SiON.…”
Section: A Impact Of High-k Materialsmentioning
confidence: 93%
“…• Effective [111,95] reduction of substrate coupling in RF circuits (allows higher quality inductors with increased Q factor)…”
Section: Soi Advantagesmentioning
confidence: 99%
“…The increase is almost one order of magnitude for the PMOS and 2-3 times larger for the NMOS. This has been related to the increased near interface oxide traps density, due to the introduction of nitride in the oxide [3]. This increase is proportional to the nitride concentration and it is measured to be a factor 2 larger for PMOS with respect to NMOS, with oxide thickness in the range 5-8.5 nm [3].…”
Section: Impact Of Nitridationmentioning
confidence: 99%
“…This has been related to the increased near interface oxide traps density, due to the introduction of nitride in the oxide [3]. This increase is proportional to the nitride concentration and it is measured to be a factor 2 larger for PMOS with respect to NMOS, with oxide thickness in the range 5-8.5 nm [3]. One could argue that the differences we measured are due to poor description of the 1/f noise spectral density by means of an oversimplified model.…”
Section: Impact Of Nitridationmentioning
confidence: 99%